An efficient method for transgenic callus induction from Vitis amurensis petiole. - Tingting Zhao; Zemin Wang; Lingye Su; Xiaoming Sun; Jun Cheng; Langlang Zhang; Sospeter Karanja Karungo; Yuepeng Han; Shaohua Li; Haiping Xin (PLoS ONE)
Transformation is the main platform for genetic improvement and gene function studies in plants. However, the established somatic embryo transformation system for grapevines is time-consuming and has low efficiency, which limits its utilization in functional genomics research. Vitis amurensis is a wild Vitis species with remarkable cold tolerance. The lack of an efficient genetic transformation system for it has significantly hindered the functional identification of cold stress related genes in the species. Herein, an efficient method was established to produce transformed calli of V. amurensis. Segments of petioles from micropropagated plantlets of V. amurensis exhibited better capacity to differentiate calli than leaf-discs and stem segments, and thus was chosen as target tissue for Agrobacterium-mediated transformation. Both neomycin phosphotransferase II (NPTII) and enhanced green fluorescent protein (eGFP) genes were used for simultaneous selection of transgenic calli based on kanamycin resistance and eGFP fluorescence. Several parameters affecting the transformation efficiency were optimized including the concentration of kanamycin, Agrobacterium stains, bacterial densities, infection treatments and co-cultivation time. The transgenic callus lines were verified by checking the integration of NPTII gene into calli genomes, the expression of eGFP gene and the fluorescence of eGFP. Up to 20% of the petiole segments produced transformed calli after 2 months of cultivation. This efficient transformation system will facilitate the functional analysis of agronomic characteristics and related genes not only in V. amurensis but also in other grapevine species.